Survei Tingkat Kesegaran Jasmani Usia 10 – 12 Tahun Pada Murid SD Negeri 57 PEPABRI Kecamatan Bara Kota Palopo - M Iqbal Hasanuddin; Hesti Meiyani Bongi (UNIVERSITAS NEGERI MAKASSSAR, 2022)
This study aimed to determine the level of physical fitness aged 10-12 years at the students of SD Negeri 57 PEPABRI, Bara District, Palopo City. This research was descriptive research. This research method was a survey with data collection technique using tests and measurments. The data analysis technique used was desckriptive percentage. The results of this study indicate that the level of physical fitness of students aged 10-12 years at SD Negeri 57 PEPABRI, Bara District, Palopo City is in very good category with a percentage of 0% (no students), good category the percentage of 3% (1 student), category while the percentage is 47% (14 student), the less percentage category is 40% (12 student), and the category the percentage of 10% (3 student). Meanwhile, based on the average value of 13.03, the level physical fitness of students aged 10-12 years at SD Negeri 57 PEPABRI, Bara District, Palopo City is in the medium category.